Chronic gingivitis: association with smoking, dental malocclusion and dental caries - María de los Angeles Labrada Fonseca; Daniel Boduet Vargas; Arimnelis Campo Alvarez; Karel Rosabal Pérez (Universidad de Ciencias Médicas de Granma, 2022)
Introduction: gingivitis has a great impact on people in terms of pain, discomfort, limitation, social and functional disability. Chronic gingivitis in adolescence has been increasing, and a scientific methodological conception is used for prevention of oral diseases in adolescence. Objective: to determine the association between chronic gingivitis and the main risk factors such as smoking, dental malocclusion and dental caries in adolescents. Method: an analytical, case-control study was carried out in seventh grade students of the Batalla de Guisa Basic Secondary School in the municipality of Guisa in the year 2021. The universe was constituted by 360 students, the sample was of 90 students, selecting 30 cases and 60 controls; a simple random sampling was applied.  The variables studied were: presence of chronic gingivitis, smoking, dental malocclusion and dental caries. Absolute and relative frequencies (percentage) were used as descriptive statistics, and the Chi-square test (x2) and the Odds Ratio (OR) were used for the association between the variables. A reliability level of 95% was adopted and a probability of error of 0.05 (p=0.05), statistical significance was accepted for p≤0.05. Results: the most frequent risk factors, in general, were dental caries (42.22 %), (p= 0.000) and dental malocclusion (52.22 %), (p= 0.006), as in those affected, in which dental malocclusion predominated. Conclusions: The association between dental caries, dental malocclusion and morbidity due to chronic gingivitis was confirmed.